Reaction to errors in robot systems - Zielinski, C. (RoMoCo'02 : proceedings of the third International Workshop on Robot Motion and Control, 2002)
The paper analyzes the problem of error (failure) detection and handling in robot programming. First an overview of the subject is provided and later error detection and handling in MRROC++ are described. To facilitate system reaction to the detected failures, the errors are classified and certain suggestions are made as to how to handle those classes of errors.